Assessment of Radial Artery Graft Patency in Symptomatic Patients - Unal, Ertekin U.; Cicekcioglu, Ferit; Ozen, Anil; Yilmaz, Metin; Kubat, Emre; Iscan, Hakki Z.; Birincioglu, Cemal L. (The Thoracic and Cardiovascular Surgeon, 2015)
Background The purpose of this study is to evaluate the patency of radial artery (RA) grafts consistent with the target vessel characteristics.Methods Between October 2001 and January 2012, 83 symptomatic patients or patients with positive ischemic test results underwent coronary angiography following coronary artery bypass grafting. Of these, 68 patients with 81 RA grafts at a mean 49.2 ± 31.9 months (range, 1–137 months) were evaluated. According to the location and degree of proximal stenosis, 5-year graft patency was determined by Kaplan–Meier analysis. The relationships between RA graft patency and degree of proximal stenosis, target vessel location, and inflow characteristics of grafts were assessed by means of Cox proportional hazard models.Results Mean age of the patients was 56.4 ± 10.2 years. The period between the operation and postoperative coronary angiography was 49.2 ± 31.9 months (range, 1–137 months; median, 48.8 months). There was no impact on RA patency with regard to preoperative characteristics of the patients. RA patency was higher for left coronary system compared with right system (p = 0.038; 85.5 vs. 65.4%). In addition, patency rate was statistically higher for the proximal stenosis ≥ 90% (odds ratio, 3.65; 95% confidence interval, 1.20–11.07; p = 0.018). Kaplan–Meier patency analysis showed a patency of RA as 79.2% at 5 years.Conclusion RA graft patency differs with degree of preoperative native coronary artery stenosis and location of target vessel. RA grafts to not severely stenosed (< 90%) coronary system and to the right coronary territory carry a remarkably high risk of graft failure.
Keywords: coronary artery bypass; radial artery; vascular patency; coronary angiography